Does legislative change affect the use and duration of compulsory treatment orders?. (May 2019) - Vine, Ruth; Tibble, Holly; Pirkis, Jane; Judd, Fiona; Spittal, Matthew J
Objective: Victoria, Australia, introduced reformed mental health legislation in 2014. The Act was based on a policy platform of recovery-oriented services, supported decision-making and minimisation of the use and duration of compulsory orders. This paper compares service utilisation and legal status after being on a community treatment order under the Mental Health Act 1986 (Vic) with that under the Mental Health Act 2014 (Vic). Methods: We obtained two distinct data sets of persons who had been on a community treatment order for at least 3 months and their subsequent treatment episodes over 2 years under the Mental Health Act and/or as an inpatient for the periods 2008–2010 (Mental Health Act 1986) and 2014–2016 (Mental Health Act 2014). The two sets were compared to assess the difference in use, duration and odds of having a further admission over 2 years. We also considered the mode of discharge – whether by the treating psychiatrist, external body or through expiry. Results: Compared with the Mental Health Act 1986, under the Mental Health Act 2014, index community treatment orders were shorter (mean 227 days compared with 335 days); there was a reduction in the mean number of community treatment orders in the 2 years following the index discharge − 1.1 compared with 1.5 (incidence rate ratio (IRR) = 0.71, 95% confidence interval = [0.63, 0.80]) – and a 51% reduction in days on an order over 2 years. There was a reduction in the number of subsequent orders for those whose order expired or was revoked by the psychiatrist under the Mental Health Act 2014 compared to those under the Mental Health Act 1986. The number of orders which were varied to an inpatient order by the authorised psychiatrist was notably greater under the Mental Health Act 2014. Conclusion: The reformed Mental Health Act has been successful in its intent to reduce the use and duration of compulsory orders in the community. The apparent increase in return to inpatient orders raises questions regarding the intensity and effectiveness of community treatment and context of service delivery.